Punctate variation among the La Crosse area Oneota ceramics after the 1500s - Strunk Williams, Kittrel (My University, 2016)
In observing the ceramic assemblage of State Road (LC34176) at the Mississippi Valley Archaeological Center, I identified unrecognized stylistic variations among the decorated sherds present. While other studies have examined the larger picture, this analysis narrows the focus to variations within punctates in relation to motifs. Each sherd was visually examined for variations in tool use, punctates, trail marks, and rim decoration. The study revealed that variation in punctates was due to tool choice, application, and motif. In addition, V-Filler/Chevron motifs were typically created with a sharp tool, whereas the Repeating Rectangle motif was primarily composed of a blunt tool. These numerous variations, described as isochrestic and symbolic variation, indicate that variation among punctates is due to individual expression and human agency. Through graphs and visual observations, variations among punctates in Oneota pottery reveal a group of people who wished to express themselves outside of the larger material culture.
Keywords: Oneota Indians (Great Plains)--Wisconsin--La Crosse; Pottery; Archaeology